DEVELOPMENT AND VALIDATION OF UV-SPECTROSCOPIC METHOD FOR ESTIMATION OF IPRATROPIUM BROMIDE IN API AND IN PHARMACEUTICAL DOSAGE FORM - SHINDE, BHAGYASHRI S.; KALSHETTI, M. S.; KOKANE, ANJALI P. (International Journal of Current Pharmaceutical Research, 2020)
Objective: To developed and validated UV spectrophotometric method for the estimation of ipratropium bromide in API and pharmaceutical formulation. Methods: Methanol is used as a solvent and the absorbance of the drug was measured at absorbance’s maxima of ipratropium bromide max is 214 nm. Results: Maximum absorbance obtained in 214 nm. Calibration curve plotted in concentration range 20-120 µm/ml exhibit the linearity relationship with line equation y=.0.0091x+0.1503 The Accuracy was found to be 99.7-100.2%, the precision %RSD= 0.08613-0.2668, and the LOD and LOQ is 6.33, 19.19. The method was found to comply all the validation parameters as per the ICH guideline indicating the sensitivity of the method analyte. Conclusion: This method is used as satisfactory for the routine analysis of ipratropium bromide in API and pharmaceutical dosage forms.